Russia And the Arab World Amid the Transformation of the International Order: A Comparative Analysis of Russia’s Relations with Egypt, Syria and Yemen (International relations and international law Journal, 2026)
This article analyzes Russia’s engagement with the Arab world in the context of the ongoing transformation of the international order, characterized by the erosion of Western dominance, the rise of multipolarity, and intensified competition among major powers. Against this backdrop, the Russian Federation has sought to expand and diversify its presence in the Middle East and North Africa, positioning itself as a flexible strategic partner for Arab states pursuing greater autonomy in foreign and economic policy.This study examines Russia’s bilateral relations with three Arab countries – Egypt, Syria, and Yemen – in order to explore how different patterns of engagement take shape across the region. These cases were selected intentionally, as they represent distinct forms of interaction, ranging from relatively stable strategic cooperation to more conflict-driven and diplomatically cautious approaches.The analysis relies on a comparative framework structured around four key dimensions: political and diplomatic interaction, economic and trade cooperation, security and military relations, and cultural and humanitarian ties. Both qualitative observations and selected quantitative indicators are used to assess the depth and character of Russia’s involvement in each case, although the availability and reliability of data differ across countries.The findings indicate that Russia does not follow a single, uniform policy model in the Middle East. Instead, its policies are adjusted to local political conditions and the stability of partner regimes. In Egypt, relations are shaped primarily by economic projects and sustained political dialogue, which together form a relatively stable basis for cooperation. Syria presents a more complex trajectory: Russia’s role, initially defined by direct military support, has gradually evolved – particularly after the political changes of late 2024 – toward a more negotiated and conditional presence. In Yemen, by contrast, Russia has maintained a relatively low-profile approach, focusing on diplomatic engagement and humanitarian issues rather than direct involvement in the conflict.Overall, Russia’s position in the Arab world cannot be described as uniform or dominant. It is better understood as context-dependent and shaped not only by broader transformations in the international system but also by the strategies of regional actors themselves. This suggests that Moscow is attempting to operate within an increasingly multipolar environment while avoiding overextension and preserving strategic flexibility.Key words: Russia, Arab world, Egypt, Syria, Yemen, foreign policy, international relations, multipolarity, economic cooperation.